Disruption of the protein C inhibitor gene results in impaired spermatogenesis and male infertility - Uhrin, Pavel (American Society for Clinical Investigation, 2000)
Protein C inhibitor (PCI) is a nonspecific, heparin-binding serpin (serine protease inhibitor) that inactivates many plasmatic and extravascular serine proteases by forming stable 1:1 complexes. Proteases inhibited by PCI include the anticoagulant activated protein C, the plasminogen activator urokinase, and the sperm protease acrosin. In humans PCI circulates as a plasma protein but is also present at high concentrations in organs of the male reproductive tract. The biological role of PCI has not been defined so far. However, the colocalization of high concentrations of PCI together with several of its target proteases in the male reproductive tract suggests a role of PCI in reproduction. We generated mice lacking PCI by homologous recombination. Here we show that PCI(–/–) mice are apparently healthy but that males of this genotype are infertile. Infertility was apparently caused by abnormal spermatogenesis due to destruction of the Sertoli cell barrier, perhaps due to unopposed proteolytic activity. The resulting sperm are malformed and are morphologically similar to abnormal sperm seen in some cases of human male infertility. This animal model might therefore be useful for analyzing the molecular bases of these human conditions.